Does clear cell carcinoma of stomach exist? Clinicopathological and prognostic significance of clear cell changes in gastric adenocarcinomas. Issue 1 (14th March 2014) - Kim, Joo‐Yeon; Park, Do Youn; Kim, Gwang Ha; Jeon, Tae‐Yong; Lauwers, Gregory Y
<x xml:space="preserve">Abstract</x> Aims In contrast to clear cell carcinomas developing in other organs (e.g. ovary and uterus), gastric adenocarcinomas with clear cell features are not well characterized. Methods and results We evaluated a series of 762 gastric adenocarcinomas for the presence of clear cell changes; and investigated the nature of the changes using several histochemical and immunohistochemical markers, their association with various clinicopathological features, and their prognostic significance. Clear cell changes were observed in 8.5% (n = 65) of gastric cancers. Cases with clear cell changes (GCC) were associated significantly with older age, intestinal type histology, body/fundic location, greater depth of invasion, lymph node metastases and lymphovascular invasion. An increasing proportion of clear cell changes indicated a worsening prognosis, and was identified as an independent marker of poor prognosis using the Cox proportional hazard model (hazard ratio, 0.462; P = 0.003). Of 62 GCCs subjected to special staining, 35 cases (55.6%) displayed cytoplasmic accumulation of glycogen, while 21 (33.3%) contained mucin. GCCs showing glycogen accumulation expressed AFP, glypican‐3 and CD10 more commonly than those with mucin, which commonly expressed Muc5AC and Muc6. Conclusion Clear cell gastric adenocarcinoma is a unique subgroup of gastric cancer which, although heterogeneous, has a poor prognosis.